Políticas de educação inclusiva e direitos de pessoas surdas: um estudo das práticas de inclusão da equipe técnica do Liceu em Parintins - Bruce, Rodrigo Machado (Brasil, 2024)
Since historical times in the past, we have observed that deaf people were treated in an inhumane way, in which they did not have access to their rights, to the social environment, much less to education, as they were previously seen as individuals lacking or incapable of obtaining knowledge. However, over the years, this individual begins to be recognized as a citizen with rights, with various legislation emerging that contributed to their inclusion in society, as well as their inclusion in educational environments. According to one of the achievements of the deaf, such as the Law of Guidelines and Bases (LDB), it can be said that education is the right of all citizens, regardless of their conditions. But it is at this moment that challenges arise when it comes to inclusion, as, currently, there is a very peculiar need in formal or non-formal, public or private teaching environments, that is, the unpreparedness of schools to receive students. deaf students appropriately. This is the case of the students interviewed in this research, since there is still no full respect and recognition of their rights in the educational space. Given the above, which is the theme discussed in this study, the present work aims to analyze the social inclusion practices of the technical team of the Liceu de Artes e Ofícios Cláudio Santoro, in Parintins, taking as a reference the rights of deaf students to courses training of the Institution. Even though the aforementioned Institution already promotes specialized assistance to students, through pedagogical practices or the support of a Libras interpreter, mediating the teaching-learning process, this is still not enough to establish the idea of inclusive education. To answer this question, bibliographical, documentary and field research was carried out; In total, 14 (fourteen) interviews took place and from this the results were analyzed. In the theoretical framework, the concepts of Inclusion Policies and Inclusive Education were discussed; Deaf culture and the deaf as subjects of rights; and the inclusion practices of Lyceum of Arts teachers regarding deaf students, chapters that were divided into topics. In terms of results, the responses of the interlocutors, for the most part, demonstrate similarities and variations when answering the questions, in which the communicational need of the teachers involved in the education process of these students was perceived, not all of whom are properly prepared to deal with the processes of inclusive education, thus ignoring the rights of deaf students.